David R. Francis, Ambassador to Four Russian Governments - Noskov, Vladimir (Journal of Russian American Studies, 2018)
This article examines the tenure of David R. Francis, U.S. ambassador to Russia from 1916 to 1918, highlighting his challenges in navigating the collapse of the Russian Empire, the rise of the Provisional Government, and the Bolshevik Revolution. Despite his lack of diplomatic experience, Francis grappled with complex issues, including prisoner-of-war management, strained U.S.-Russian relations, and Allied intervention efforts. The author argues that Francis’ performance reflects broader shortcomings of Wilsonian diplomacy, characterized by liberal illusions and democratic prejudices ill-suited to revolutionary Russia. Through a critical analysis of Francis’ actions and memoirs, the article questions his legacy while situating his failures within the context of U.S. foreign policy under Woodrow Wilson.